Adolescent Substance Abuse Evidence-Based Approaches to Prevention and Treatment (Issues in Children's and Families' Lives,, 2018)
The second edition of this book incorporates the latest theory, research, and best practices for understanding, treating, and preventing substance abuse among adolescents. It updates the progress made in treatments for and prevention of the misuse of substances and adds new specific chapters on prescriptions, opiates, and methamphetamine abuse. The book discusses the effects of commonly abused substances, from tobacco and alcohol to stimulants and opioids, on the human brain and the various psychosocial routes to their misuse by adolescents. Chapters provide evidence-based guidelines for assessing adolescent treatment needs and review psychological, pharmacological, family, and self-help interventions. The book offers new paths in diverse directions, analyzes the core components of substance use prevention, critiques emerging school-based interventions, and introduces a nuanced reconceptualization of recovery. Topics featured in the book include: The effect of family and caregiver situations on adolescent substance abuse. A biological/genetic perspective on adolescent substance abuse. School-based preventions and the evolution of evidence-based strategies. The role of adolescent self-help in substance abuse interventions. Community-based interventions to reduce alcohol use and misuse. Adolescent Substance Abuse, Second Edition, is a must-have reference for researchers, clinicians/practitioners, and graduate students in the fields of child and school psychology, social work, public health, developmental psychology, child and adolescent psychiatry, and various interrelated mental health and social policy arenas.